Preoperative staging of rectal cancer. (October 2009) - Yeung, Justin MC; Ferris, Nicholas J; Lynch, A Craig; Heriot, Alexander G
Preoperative staging is now an essential factor in the multidisciplinary management of rectal cancer because tumor stage is the strongest predictive factor for recurrence. Preoperative staging of rectal cancer can be divided into either local or distant staging. Local staging incorporates the assessment of mural wall invasion, circumferential resection margin involvement, as well as the nodal status for metastasis. Distant staging assesses for evidence of metastatic disease. The aim of this review is to consider the indications and limitations of the current preoperative imaging modalities for rectal cancer staging including clinical examination, endorectal ultrasound, magnetic resonance imaging, computed tomography and positron emission tomography––computed tomography, with respect to local and distant disease.